2018
DOI: 10.1002/smll.201803584
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Reduced Graphene Oxide as a High Capacity Cathode for Aluminum Batteries

Abstract: Research in the field of aluminum batteries has focused heavily on electrodes made of carbonaceous materials. Still, the capacities reported for these multivalent systems remain stubbornly low. It is believed that a high structural quality of graphitic carbons and/or specific surface areas of >1000 m2 g‐1 are key factors to obtain optimal performance and cycling stability. Here an aluminum chloride battery is presented in which reduced graphene oxide (RGO) powder, dried under supercritical conditions, is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 53 publications
(99 reference statements)
1
55
0
Order By: Relevance
“…The most researched component for aluminum-ion batteries is the cathode. The research can be divided into six groups based on the type of material used for the cathode: metal oxides [127][128][129][130][131][132], metal sulfides [133][134][135][136][137], carbon [138,139], metal selenides [14,140] metal phosphides [141,142] and metal phosphite [143]. Here we highlight those works that focus on the function of the material.…”
Section: Aluminum-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most researched component for aluminum-ion batteries is the cathode. The research can be divided into six groups based on the type of material used for the cathode: metal oxides [127][128][129][130][131][132], metal sulfides [133][134][135][136][137], carbon [138,139], metal selenides [14,140] metal phosphides [141,142] and metal phosphite [143]. Here we highlight those works that focus on the function of the material.…”
Section: Aluminum-ion Batteriesmentioning
confidence: 99%
“…It is generally believed that the structural quality of graphitic carbons assists in improving the performance of Al-ion batteries [146][147][148]. However, a different approach was also reported, where mesoporous reduced graphene oxide was designed and used as cathode to improve the performance of Al-ion batteries [139]. The material shows electrochemical performance comparable to that of material with much larger surface areas.…”
Section: Carbon-based Materials As Cathodes In Al-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…designed the cell with 3D foam graphite cathode, which delivered a voltage platform up to 2 V and long‐term stability . Afterwards, a variety of carbon materials have been explored, mainly including edge‐rich graphene paper, mesoporous reduced graphene oxide, MOF‐derived carbon heterostructures, graphene aerogel derived compact films, polythiophene/graphite composites, graphene nanoribbons on highly porous 3D graphene, defect‐free soft carbon, amorphous carbon‐graphite composite, carbon nanoscrolls and commercial expanded graphite . All kinds of carbon materials exhibit a reversible capacity of 60–130 mA h g −1 and unparalleled cycle stability.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, [2] we reported that the pore size distribution of the active material had a decisive effect on the electrochemical performance of aluminum chloride batteries (ACBs). Here, we show that the choice of the binder/solvent pair is another factor to carefully assess in the optimization of ACBs.…”
Section: Introductionmentioning
confidence: 99%